"The Circle of Life Is Endless": Shih Li-Jen's "King Kong Rhino" in Venice and beyond. Issue 1 (2nd January 2021) - Dickenson, Jackie
Abstract: When "King Kong Rhino"—the monumental–sculpture by the Taiwanese artist Shih Li-Jen (1955–) left Venice for Bassano del Grappa in December 2018, it joined a distinguished line of rhinoceroses to have embarked on a European tour. This article examines the place of Shih's rhinoceros sculptures in this "Endless Circle of Life, " beginning with the European journeys of two historical rhinoceroses, Ganda who arrived in Portugal in 1515, and Clara who was displayed in Venice in 1751. The article outlines Shih's idiosyncratic collage of themes from Eastern and Western history, philosophy, spirituality and mythology, and his perception of the rhinoceros as powerful but threatened, as expressed in his motto "Strength and Vulnerability." The animal's vulnerability has been fuelled by its long history of exploitation for profit. Though it remains an object of commodification today—in some societies rhinoceros horn is revered as the ultimate gift—there has recently been a discernible shift in the way these magnificent animals are viewed, a shift away from exploitation and which Shih claims drives his work. Despite his expressed intentions, however, this paper suggests that, perhaps unwittingly, the marketing of his work serves to extend the long history of human exploitation of the rhinoceros. Finally, the commodification of Venice and its Biennale, at which "King Kong Rhino" was exhibited, is discussed in the context of the current COVID-19 pandemic.